1997
DOI: 10.1080/096031097333312
|View full text |Cite
|
Sign up to set email alerts
|

Security price anomalies in the London International Stock Exchange: a 60 year perspective

Abstract: This paper investigates the existence of security price anomalies, or 'calendar effects' in the Financial Times Industrial Ordinary Shares Index over a 60 year period: 1 July 1935 through 31 December 1994. Our results broadly support similar evidence documented for many countries concerning stock market anomalies, as the weekend, January and holiday effects all appear, to some extent, to be present in our data set. We conclude, that even if these anomalies are persistent in their occurrence and magnitude, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 36 publications
8
40
0
Order By: Relevance
“…This is in agreement with the previous literature such as Mills and Coutts (1995) and Arsad and Coutts (1997). The second conclusion is that once transactions costs have been accounted for, the day of the week effect seems to no longer be an enduring anomaly.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with the previous literature such as Mills and Coutts (1995) and Arsad and Coutts (1997). The second conclusion is that once transactions costs have been accounted for, the day of the week effect seems to no longer be an enduring anomaly.…”
Section: Discussionsupporting
confidence: 92%
“…The conventional methodology employed in the anomalies' literature was utilized in order to test for a day of the week effect (see Arsad and Coutts, 1997). Thus, daily returns are regressed on five dummy variables each one representing a day of the working week to see whether there is any statistically significant difference among returns on different days: The methodology used is shown in Equation 1.…”
Section: The Day Of the Week Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, it has been found that the weekend return (i.e., the return from the close on Friday to the opening on Monday) is lower than the daily returns during the week (Arsad and Coutts 1997, Franses and Paap 2000, French, 1980, Keim and Stambaugh, 1984, Lakonishok and Smidt, 1988, Rogalski, 1984. There have been a variety of (modestly successful) attempts at explaining this phenomenon (e.g.…”
Section: Resultsmentioning
confidence: 99%